PENGARUH RELATIONSHIP MARKETING, SERVICE QUALITY DAN FASILITAS TERHADAP LOYALITAS PELANGGAN (Studi Kasus Pada Kedai Kopi Sor Sawo Ponorogo) - Anggun Pangastuti; Edi Santoso; Sri Hartono (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2022)
The development of the coffee shop business in Ponorogo is currently increasing, almost all over the city we can find coffee shops. The existence of a coffee shop for young people is an alternative to take advantage of free time, study or other purposes. The existence of a coffee shop or coffee shop that continues to increase makes the competition in this business market even tighter. The purpose of this study was to determine and examine the effect of Relationship Marketing, Service Quality and Facilities on Customer Loyalty (a case study at Sor Sawo Ponorogo coffee shop). The research used is quantitative research. Data collection in this study is primary data obtained from the distribution of questionnaires. The number of samples consisted of 100 people, using accidental sampling technique. The results showed that: (1) Relationship Marketing had a positive and significant effect on customer loyalty at the Sor Sawo Ponorogo coffee shop. The research used is quantitative research. Data collection in this study is primary data. (2) Service Quality has a positive and significant effect on customer loyalty at the Sor Sawo Ponorogo coffee shop. The research used is quantitative research. Data collection in this study is primary data. (3) Facilities have a positive and significant effect on customer loyalty at the Sor Sawo Ponorogo coffee shop.